Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah PT. Bank Mega Cabang Sengkang - Ekayani Burhanuddin; Maspawati Tokang; Erna Erna (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
this article is the result of an analysis of customer satisfaction with PT. Bank Mega Sengkang branch. In connection with this, how do customers get the service they expect with the provision of services from staff or employees so that customers feel happy and their wishes are fulfilled. Therefore, this study aims to show the significance of the influence of service quality on customer satisfaction. In analyzing the data, descriptive analysis was used which contained the distribution of items from each variable, then simple linear regression analysis and hypothesis tester. From the results of the tester with simple linear regression and partial regression analysis, it was shown that the simultaneous variable of Service (X) to customer satisfaction (Y) indicated by the R square value was 0.462. This figure shows that the simultaneous variable Service (X) used in this regression equation contributes to customer satisfaction (Y) of 46.2% while the remaining 53.8% is explained by other factors that are not included in this study. Based on the results of this study, it was concluded that customer satisfaction had a significant and partially positive effect on the increase in the number of customers at PT. Bank Mega Sengkang branch.